Principles of marketing - Kotler, Philip (Pearson, 2015)
In a fast-changing, increasingly digital and social marketplace, it’s more vital than ever for marketers to develop meaningful connections with their customers. Principles of Marketing helps students master today’s key marketing challenge: to create vibrant, interactive communities of consumers who make products and brands an integral part of their daily lives. To help students understand how to create value and build customer relationships, Kotler and Armstrong present fundamental marketing information within an innovative customer-value framework